Investment and public communications of science is a priority: Interview with Ángela Posada-Swafford - Medina Morales, Gladys del Carmen; Cuevas Gómez, Martha Elena (Emerging Trends in Education, 2021)
The convergence between public policies, scientists and journalists will permit a meaningful public communication of science for society in critical moments like the ones we live because of the global threath of the COVID-19 pandemic, said Ángela Posada-Swafford, world-renowned scientific journalist.